Molecular Diagnosis of Infectious Diseases
DOI: 10.1385/0-89603-485-2:169
|View full text |Cite
|
Sign up to set email alerts
|

Application of TEV Protease in Protein Production

Abstract: In many cases, the analysis of a specific protein is impeded by the inability to purify large amounts of it from a native source. Proteins of interest may be present in minute quantities and/or purification may be plagued with technical problems. Recombinant DNA methodologies have enabled researchers to circumvent some of these limitations by producing and purifying large quantities of protein in a nonnative system. Various systems and strategies have been successfully employed, depending on the specific prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In the same study, the enzyme was reported to be relatively insensitive to NaCl concentrations between 0.1 and 2.0 M. In a later study, TEV protease activity was observed to be greatest in the absence of monovalent salt, but decreased only moderately at NaCl concentrations up to 200 mM [73]. Although the optimum temperature for TEV protease activity is 30-34°C, the enzyme retains significant activity at 4°C [73,74]. Activity drops off abruptly above 37°C, probably due to denaturation of the enzyme [73].…”
Section: Tev Proteasementioning
confidence: 85%
“…In the same study, the enzyme was reported to be relatively insensitive to NaCl concentrations between 0.1 and 2.0 M. In a later study, TEV protease activity was observed to be greatest in the absence of monovalent salt, but decreased only moderately at NaCl concentrations up to 200 mM [73]. Although the optimum temperature for TEV protease activity is 30-34°C, the enzyme retains significant activity at 4°C [73,74]. Activity drops off abruptly above 37°C, probably due to denaturation of the enzyme [73].…”
Section: Tev Proteasementioning
confidence: 85%
“…The gene encoding PglK from C. jejuni was cloned into a modified pET-19b vector (Novagen) with a N-terminal His10 affinity tag and a TEV protease cleavage site34. PglK was overexpressed in E. coli BL21-Gold (DE3) (stratagene) cells, which were grown at 37 °C in Terrific Broth medium supplemented with 1% glucose (w/v) and induced with 0.2 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
“…Native elution from SpA/IgG affinity systems generally follows two lines: competitive elution of the tagged bait protein and its coprecipitated interactors (7,8), or protease cleavage of the tag from the bait protein, releasing the bait and its coprecipitated interactors (3). The efficiency of release of different protein complexes from the stationary phase by protease cleavage is not uniform, and cleavage requires long incubation times ranging from hours to overnight (9,10). Improvement of these parameters, if at all possible, would likely require fundamental engineering of the protease.…”
mentioning
confidence: 99%